Submarine groundwater discharge: A previously undocumented source of contaminants of emerging concern to the coastal ocean (Sydney, Australia). (November 2020) - McKenzie, Trista; Holloway, Ceylena; Dulai, Henrietta; Tucker, James P.; Sugimoto, Ryo; Nakajima, Toshimi; Harada, Kana; Santos, Isaac R.
Abstract: Submarine groundwater discharge (SGD) is rarely considered as a pathway for contaminants of emerging concern (CECs). Here, we investigated SGD as a source of CECs in Sydney Harbour, Australia. CEC detection frequencies based on presence/absence of a specific compound were >90% for caffeine, carbamazepine, and dioxins, and overall ranged from 25 to 100% in five studied embayments. SGD rates estimated from radium isotopes explained >80% of observed CEC inventories for one or more compounds (caffeine, carbamazepine, dioxins, sulfamethoxazole, fluoroquinolones and ibuprofen) in four out of the five embayments. Radium-derived residence times imply mixing is also an important process for driving coastal inventories of these persistent chemicals. Two compounds (ibuprofen and dioxins) were in concentrations deemed a high risk to the ecosystem. Overall, we demonstrate that SGD can act as a vector for CECs negatively impacting coastal water quality. Highlights: Submarine groundwater discharge transports pharmaceuticals to the coastal ocean. There is a relationship between residence times and micropollutant inventories. Ibuprofen and dioxins pose an ecological risk to Sydney Harbour.